A rare case of postmenopausal hyperandrogenism due to ovarian hyperthecosis and hilus cell hyperplasia. Issue 1 (March 2022) - Johnson, Jean-Ellen; Hussain, Munawar; Rathore, Ali; Wolfe, Konrad
Postmenopausal hyperandrogenism is rare, and without consensus on specific investigative indices, diagnosis is challenging. A 77-year-old woman had a three-year history of hirsutism, male-pattern baldness and increased libido alongside elevated androstenedione, total testosterone and free androgen index levels. A magnetic resonance imaging (MRI) scan showed bilateral ovarian lesions, suggesting ovarian hyperthecosis. Histopathology obtained after a laparoscopic bilateral salpingo-oophorectomy confirmed ovarian hyperthecosis and hilus cell hyperplasia. We believe it's the first time they have been reported to occur in combination. The symptoms resolved within a month of surgery. This case highlights the difficulties of diagnosis alongside demonstrating the importance of management by a multidisciplinary team.